Diversity of Astroglial Effects on Aging- and Experience-Related Cortical Metaplasticity - Lalo, Ulyana; Bogdanov, Alexander; Pankratov, Yuriy (Frontiers in Molecular Neuroscience, 2018)
Activity-dependent regulation of synaptic plasticity, or metaplasticity, plays a key role in the adaptation of neuronal networks to physiological and biochemical changes in aging brain. There is a growing evidence that experience-related alterations in the mechanisms of synaptic plasticity can underlie beneficial effects of physical exercise and caloric restriction (CR) on brain health and cognition. Astrocytes, which form neuro-vascular interface and can modulate synaptic plasticity by release of gliotransmitters, attract an increasing attention as important element of brain metaplasticity. We investigated the age- and experience-related alterations in astroglial calcium signaling and stimulus-dependence of long-term synaptic plasticity in the neocortex of mice exposed to the mild CR and environmental enrichment (EE) which included ad libitum physical exercise. We found out that astrocytic Ca2+-signaling underwent considerable age-related decline but EE and CR enhanced astroglial signaling, in particular mediated by noradrenaline (NA) and endocannabinoid receptors. The release of ATP and D-Serine from astrocytes followed the same trends of age-related declined and EE-induced increase. Our data also showed that astrocyte-derived ATP and D-Serine can have diverse effects on the threshold and magnitude of long-term changes in the strength of neocortical synapses; these effects were age-dependent. The CR- and EE-induced enhancement of astroglial Ca2+-signaling had more stronger effect on synaptic plasticity in the old (14–18 months) than in the young (2–5 months) wild-type (WT) mice. The effects of CR and EE on synaptic plasticity were significantly altered in both young and aged dnSNARE mice. Combined, our data suggest astrocyte-neuron interactions are important for dynamic regulation of cortical synaptic plasticity. This interaction can significantly decline with aging and thus contributes to the age-related cognitive impairment. On another hand, experience-related increase in the astroglial Ca2+-signaling can ameliorate the age-related decline.